1998
DOI: 10.1097/00003246-199810000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intravenous terbutaline for pediatric status asthmaticus

Abstract: Intravenous terbutaline was well tolerated in asthmatic children for < or =305 continuous hours and at varying doses up to a maximum of 10 microg/kg/min. There was no relationship between the magnitude of CPK-MB concentrations and the terbutaline or epinephrine doses used. Arrhythmias were rare and not related to either terbutaline or epinephrine doses. However, ST-segment depression did occur in two patients requiring high-dose epinephrine. Terbutaline significantly lowered DBP when used between 0.4 and 1.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
9

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 8 publications
0
19
0
9
Order By: Relevance
“…There is increasing evidence that ␤ 2 -AR agonists can reduce BP and renal function (10 -12). Stephanopoulos et al (10) reported that ␤ 2 -AR agonists significantly decreased diastolic BP in children with asthma. On the other hand, Hashimoto et al (11) indicated that urine flow, glomerular filtration, renal blood flow, free water clearance and excretion of electrolytes were reduced by administration of ␤ 2 -AR agonists which was associated with a concomitant fall in systemic BP.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that ␤ 2 -AR agonists can reduce BP and renal function (10 -12). Stephanopoulos et al (10) reported that ␤ 2 -AR agonists significantly decreased diastolic BP in children with asthma. On the other hand, Hashimoto et al (11) indicated that urine flow, glomerular filtration, renal blood flow, free water clearance and excretion of electrolytes were reduced by administration of ␤ 2 -AR agonists which was associated with a concomitant fall in systemic BP.…”
Section: Discussionmentioning
confidence: 99%
“…55 To accelerate the therapeutic effect, an intravenous loading dose of 2 to 10 mcg/kg infused for 10 minutes is recommended, followed by a continuous infusion of 0.1 to 10 mcg/kg/min. 83 Because of differences in drug metabolism and clinical effect among patients, dose adjustment should be assessed at regular intervals. Usually the starting dose is 0.4 mcg/kg/min; it is titrated to achieve the desired clinical effect with increments of 0.2 to 0.4 mcg/ kg/min every 15 to 30 minutes depending on the patient's clinical response and on adverse drug reactions.…”
Section: Terbutalinementioning
confidence: 99%
“…82 The most reported adverse drug reactions with β-agonists are tachycardia, tremors, and nausea. Cardiovascular effects include diastolic hypotension, 83 arrhythmias, and prolonged QTc interval with hypokalemia. 84 Hypokalemia is the result of intracellular potassium shifting from an increased number of sodium-potassium pumps.…”
mentioning
confidence: 99%
“…A dose máxima referida seria de 4 µg/kg/min. Atualmente, uma vez iniciada a infusão em taxas de 1 µg/kg/min, aumenta-se o aporte da droga em intervalos freqüentes, até obtenção de uma resposta clínica desejada, ou o aparecimento de sinais relacionados a uma não tolerância por parte do paciente, podendo atingir taxas de infusão de 10 a 15 µg/kg/min 8,30,34,[37][38][39] . Recentemente, baseado na farmacocinética e na farmacodinâmica destas drogas, Shan sugeriu um novo protocolo para condução da infusão.…”
Section: Terapia Intravenosa: Papel Dos ß 2 -Agonistasunclassified